Controle robusto chaveado de sistemas lineares variantes no tempo com aplicação em falhas estruturais - Buzachero, Luiz Francisco Sanches [UNESP] (2014)
This thesis presents results for robust stability of linear systems subject to polytopic timevarying parametric uncertainties (LPV). To start with, an improved method for the optimal gain design of robust controllers via Linear Matrix Inequalities (LMI), based on Lyapunov stability theory is presented. This new formulation was manipulated using the Finsler lemma, which enabled finding better feasibility results with the addition of extra matrices and reducing the number of LMIs. In this new equation it was included the decay rate performance index, responsible for reducing the transitional period time, as well as the controllers norm optimization, responsible for lower gains while maintaining the same project requirements efficiency. Then, due to important results in literature regarding the design of robust controllers with time-varying uncertainties, the design of switched dynamic controllers was explored by including the decay rate index and the optimization of the switched controllers norm in the equation, which allowed finding better implementation results. Finally, less conservative criteria were proposed for stability analysis and design of switched controllers using minimum-type piecewise quadratic Lyapunov functions. The advantage of this procedure lies in the increase of relaxation parameters, however, designed through formulations based on Bilinear Matrix Inequalities (BMIs), where the bilinear terms are in the product between optimization scalar variables and matrices, which are also variables on the optimization procedure. Numerical examples are presented and simulated to illustrate the efficiency of the proposed methodologies in relation to other existing throughout the text. The designed controllers were implemented using these new proposals in a Three Degrees Of Freedom (3-DOF) helicopter or in the Shake Table II (STII) + Active Mass Dumper - One Floor (AMD-1) system, in order to validate in practice the proposed theories